Pre-operative haematological investigations in paediatric orofacial cleft repair: Any relevance to management outcome? - Anthony T Adenekan; Aramide F Faponle; Fadekemi O Oginni (Wolters Kluwer Medknow Publications, 2012)
Aim and Objectives: To determine the value of routine pre-operative haematologic investigations in children undergoing orofacial cleft repair. Background: Although routine pre-operative laboratory screening tests are carried out traditionally, some studies suggest that they are not absolutely necessary in the management of elective surgical patients. Materials and Methods: This is a prospective cohort study carried out at a tertiary health facility located in Nigeria. A review of the laboratory investigations in 116 paediatric orofacial cleft patients undergoing surgery during a 6-year period was undertaken. Pre-operative laboratory investigations and peri-operative transfusion records were analysed for the frequency and impact of abnormal results on treatment plan and outcome using the Statistical Packages for the Social Scientists 16.0. Results: All the children had pre-operative packed cell volume (PCV) check on admission for surgery. The PCV ranged from 23% to 43%, mean was 32.9 (±3.7%). Twenty-two children (18.6%) had sub-optimal PCV (<30%). Patients with the lowest PCV values (23% and 26%) were transfused pre-operatively. The lowest post-operative PCV was 23%, mean 30.8 (±3.3%). There was no occasion of post-operative blood transfusion. Eighty-six patients (72.9%) had full or partial serum electrolyte and urea analysis. Screening for sickle-cell disease was rarely done. Fourteen intra- and post-operative complications were recorded. None of these were predictable by the results of pre-operative screening tests carried out. All the children were discharged home in satisfactory condition. Conclusions: Routine laboratory testing has minimal impact on management and outcome of orofacial cleft surgeries. However, haematocrit screening may be appropriate, particularly in clinically pale patients.